The fall guy : a novel - Lasdun, James (W. W. Norton & Company, 2016)
It is summer, 2012. Charlie, a wealthy banker with an uneasy conscience, invites his troubled cousin Matthew to visit him and his wife in their idyllic mountaintop house. As the days grow hotter, the friendship between the three begins to reveal its fault lines, and with the arrival of a fourth character, the household finds itself suddenly in the grip of uncontrollable passions. As readers of James Lasdun's acclaimed fiction can expect, The Fall Guy is a complex moral tale as well as a gripping suspense story, probing questions of guilt and betrayal with ruthless incisiveness. Who is the real victim here? Who is the perpetrator? And who, ultimately, is the fall guy?